Traits of benthic assemblages subjected to different trawling pressure - Alves, Fábio Rui Lima (2014)
Over time, fishing techniques improved as a response to the needs of Human populations. Alongside with the increase of fishing activities important changes in the marine ecosystems were also observed (e.g. overexploitation of stocks and habitat loss or degradation). Overfishing, bycatch, discards and ghost-fishing are some of the most discussed impacts of fishing activities, but the effect of bottom trawling should not be underestimated, since it has been proven to have a significant impact of benthic communities. Up to now the knowledge about fisheries impact on deep-sea benthic macrofaunal assemblages is scarce in Europe and, for all we know, even more in Portuguese fishery grounds. However, assessing fisheries impacts on marine ecosystems and ensuring fisheries sustainability is essential to achieve proper management of the sector and for the conservation of marine resources. In this context, the present study was carried out aiming to investigate the impact of continued trawling on benthic macrofaunal assemblages from deep muddy grounds of the burrowing crustacean Nephropsnorvegicus (Norway lobster) by comparing towed and untowed stations regarding their biodiversity, density, biomass, trophic structure, life style and body size spectra. Seven stations were studied along a transect of a highly Fished zone (Area 1, Stations 1 and 2), a Non-fished zone (Area 2, Stations 3, 4 and 5) and another Fished zone (Area 3, stations 6 and 7) during a cruise carried out in September 2012 onboard the RV Garcia del Cid (Consejo Superior de Investigaciones Cientificas) in the framework of the project IMPACT (Universidade do Algarve). In general Fished zones showed decreased heterogeneity and although the results of the multivariate analysis support a significant difference between Fished and Non-fished areas the comparisons of the biodiversity (number of families, H’, EF(n)), density and biomass in Fished and Non-fished zones are inconclusive, inconsistent or even contradict most of the literature predictions. When the trophic structure and life style spectra of the assemblages are compared the decreased heterogeneity of the Fished zones is confirmed but other patterns emerge such as the higher relative contribution of free living organisms, especially meiofaunal predators, grazers and browsers in Fished zones in contrast with the higher relative contribution of tubiculous animals in Non-fished zones, the dominance of deposit feeders over detritus feeders in Fished areas and the presence of large suspension feeders in Non-fished zones. The interpretation of the observed taxonomic and trophic structure of the assemblages is complex and must take into account sources of variability introduced by unwanted alterations of the sampling strategy and habitat heterogeneities in the study area. Overall this study constitutes a good asset for the knowledge of bottom trawling impact on macrofaunal assemblages from deep-sea habitats. It is at this point impossible to estimate the impact of 60 years of bottom trawling and regular monitoring studies are desirable. Some methodological issues arose which can be used as recommendations for future assessments of trawling impacts and monitoring of seafloor integrity: selection of adequate control area(s) must consider habitat heterogeneity, selection of the sampling gear must consider the possible selectivity of smaller samplers; the number of replicates per stations should be sufficiently large to ensure representativeness of biodiversity, abundance and biomass assessment and significance of the comparative tests; and finally, trophic structure, life style and body size spectra showed to be good indicators of change and therefore they should become a more common tool on the assessment of trawling impact.